(untitled) (Terr@ Plural, 2021)
Environmental interpretation is a tool that helps in understanding the landscape and its elements, frequently used in protected areas (PA) to sensitize visitors. To improve environmental interpretation and promote bird watching in the Campos Gerais National Park, this paper aims to discuss the importance of interpretative means to achieve the objectives of the PA, presenting a proposal for a panel and a folder of the present avifauna. For this, besides the bibliographical research and expert consulting, we carried out field visits. It is concluded that the proposed tools could improve the interpretation/identification, as well as in the promotion of sustainable tourism potential in the conservation of birdlife.